2022
DOI: 10.3390/ijms23031780
|View full text |Cite
|
Sign up to set email alerts
|

The SDF1-CXCR4 Axis Is Involved in the Hyperbaric Oxygen Therapy-Mediated Neuronal Cells Migration in Transient Brain Ischemic Rats

Abstract: Neurogenesis is a physiological response after cerebral ischemic injury to possibly repair the damaged neural network. Therefore, promoting neurogenesis is very important for functional recovery after cerebral ischemic injury. Our previous research indicated that hyperbaric oxygen therapy (HBOT) exerted neuroprotective effects, such as reducing cerebral infarction volume. The purposes of this study were to further explore the effects of HBOT on the neurogenesis and the expressions of cell migration factors, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Several experimental and clinical studies also showed a beneficial effect from HBOT in brain/cerebral injuries [41][42][43]. Animal studies have shown the inhibitory effect of HBOT on inflammation and apoptosis after cerebral ischemia [41,44]. Furthermore, these studies have shown that HBOT is associated with reduced blood-brain barrier breakdown, reduced cerebral edema, improved cerebral oxygenation, decreased intracranial pressure, reduced oxidative burden, reduced metabolic derangement, and increased neural regeneration [41,42,45].…”
Section: Clinical Application Of Hbotmentioning
confidence: 97%
“…Several experimental and clinical studies also showed a beneficial effect from HBOT in brain/cerebral injuries [41][42][43]. Animal studies have shown the inhibitory effect of HBOT on inflammation and apoptosis after cerebral ischemia [41,44]. Furthermore, these studies have shown that HBOT is associated with reduced blood-brain barrier breakdown, reduced cerebral edema, improved cerebral oxygenation, decreased intracranial pressure, reduced oxidative burden, reduced metabolic derangement, and increased neural regeneration [41,42,45].…”
Section: Clinical Application Of Hbotmentioning
confidence: 97%
“…Additionally, HBOT increases the expression of BDNF, further facilitating the reconstruction of impaired neural networks and potentially contributing to the restoration of motor function. The involvement of the ROS/HIF-1α/β-catenin pathway in these processes has also been suggested [97]. Functional electrical stimulation has been reported to promote neurogenesis in the brains of acute ischemic stroke rats.…”
Section: Other Types Of Interventionsmentioning
confidence: 99%
“…Currently, HBOT is considered both alone and in combination with different antibacterial treatment a relevant option for solving several cute or chronic diseases [249,251,257,258]. Although animal studies have shown the inhibitory effect of HBOT on inflammation and apoptosis after cerebral ischemia [259,260], clinical trials on humans have not shown any significant benefit. Anyway, it has been indicated that HBOT can improve some neuropsychological and inflammatory outcomes, especially in stroke patients, within the first few hours [261,262].…”
Section: Clinical Application Of Hbot In Infectionsmentioning
confidence: 99%